Accurate and Sensitive Analytical Strategy for the Determination of Antimony: Hydrogen Assisted T-Shaped Slotted Quartz Tube-Atom Trap-Flame Atomic Absorption Spectrometry - Unutkan, Tugce; Koyuncu, Ikbal; Diker, Cansu; Firat, Merve; Buyukpinar, Cagdas; Bakirdere, Sezgin (SPRINGER, 2019)
Antimony is known to have some adverse health effects on human health. Flame atomic absorption spectrometry (FAAS) is a widely used instrumental for the determination of antimony and other metals. However, it lacks the sensitivity to determine these metals at trace levels. This study was aimed at overcoming this setback by using hydrogen assisted T-shaped slotted quartz tube technique to preconcentrate and determine antimony by FAAS. All the system parameters were optimized to enhance the detection power of the system. Under the optimum experimental conditions, the limits of detection and quantification were found to be 0.75 and 2.49 mu gL(-1), respectively with R-2 value of 0.9999. Accuracy of the developed method was validated by experimental results agreeing to the certified value of a standard reference material. Recovery studies were also carried out to determine the method's applicability to tap and mineral water samples, and the results obtained were appreciable.
Keywords: Antimony; FAAS; T-SQT; Atom trap; Hydrogen; INORGANIC ANTIMONY; NATURAL-WATERS; LEAD; PRECONCENTRATION; SPECIATION; IMPROVEMENT; CADMIUM; COPPER; Environmental Sciences & Ecology; Toxicology